Self and Other Mentalizing Polarities and Dimensions of Mental Health: Association With Types of Symptoms, Functioning and Well-Being - Ballespí, Sergi; Vives, Jaume; Sharp, Carla; Chanes, Lorena; Barrantes-Vidal, Neus (Frontiers in Psychology, 2021)
Research suggests that the ability to understand one’s own and others’ minds, or mentalizing, is a key factor for mental health. Most studies have focused the attention on the association between global measures of mentalizing and specific disorders. In contrast, very few studies have analyzed the association between specific mentalizing polarities and global measures of mental health. This study aimed to evaluate whether self and other polarities of mentalizing are associated with a multidimensional notion of mental health, which considers symptoms, functioning and well-being. Additionally, the level or depth of mentalizing within each polarity was also analyzed. A sample of 214 adolescents (12-18 years old, M = 14.7, SD = 1.7; 53.3% female) was evaluated on measures of self- (Trait Meta-Mood Scale or TMMS-24) and other- mentalizing (Adolescent Mentalizing Interview or AMI), multi-informed measures of psychopathology and functioning based on Achenbach’s system (ASEBA), and measures of psychological well-being (self-esteem, happiness and motivation to life goals). Results revealed no association between mentalizing polarities and higher-order symptom factors (internalizing, externalizing, and global symptoms or ‘p’ factor). Self-mentalizing was associated with self-esteem (B=0.076, p<0.0005) and motivation to life goals (B=0.209, p=0.002), and other-mentalizing was associated to general, social and role functioning (B=0.475, p<0.0005; B=0.380, p=0.005; B=0.364, p=0.004). This association between aspects of self-other mentalizing and self-other function has important implications for treatment and prevention. Deeper mentalizing within each polarity (i.e., comprehension beyond simple attention to one’s own mental states, and mentalizing referred to attachment figures versus mentalizing referred to the characters of a story) revealed stronger associations with functioning and well-being. Because mentalizing polarities are associated with functioning and well-being but not with symptoms, a new hypothesis is developed: mentalizing does not contribute to resiliency by preventing symptoms, but by helping to deal with them, thus improving functioning and well-being independently of psychopathology. These findings support that promoting mentalizing across development may improve mental health, even in non-clinical population.